Planning and Implementing Student-Led IEPs for Students With EBD. (August 2019) - Davis, Mariya T.; Cumming, Ingrid K.
Students with emotional and behavioral disorders (EBD) have difficulties in transitioning to postschool environments. Research has documented that postsecondary outcomes for students with EBD in the areas of education, employment, and community participation continue to be limited and, therefore, in need of improvement. Some of the outcomes relate to how transition programs integrate effective practices to support students with EBD. In this article, we describe a student-led Individualized Education Program (IEP) practice and provide step-by-step directions that can be used for planning and conducting student-led IEPs.